2020
DOI: 10.1111/modl.12662
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Versus Holistic Recognition of Chinese Words Among L2 Learners

Abstract: In studying the relationship between word recognition and reading development, a distinction is made between analytic and holistic processing of words. These strategies are often assessed in a length effect in an alphabetic language or in a stroke‐number effect in a logographic language. Analytical processing is associated with a robust length or stroke‐number effect while holistic processing is reflected in smaller or a lack of such effects. Research has shown that skilled readers employ holistic processing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…In constructing the path model demonstrating the direct and indirect effects of character reading on comprehension, we put the OKC as the first mediator followed by the OKCC as the second one based on the following assumptions: (a) Following a bottom-up approach in reading ( Gough, 1972 ; LaBerge and Samuels, 1974 ), reading is a process starting from the recognition of the smallest linguistic units (i.e., character) to larger units (words, clauses, sentences, and paragraphs). As hypothesized in the literature, the lexical orthographic knowledge could help readers surpass character-level reading and achieve quickly and fluently comprehend text at higher linguistic levels such as sentence- and text-levels ( Ziegler et al, 2003 ; Jiang et al, 2020 ). Therefore, it was reasonable to arrange the variables with regard to the fine-grained linguistic units; (b) In terms of task difficulty, we considered OKCC was more challenging than OKC to CSL students because they had to additionally recognize characters and understand the context of sentences in order to complete the task.…”
Section: The Present Studymentioning
confidence: 84%
“…In constructing the path model demonstrating the direct and indirect effects of character reading on comprehension, we put the OKC as the first mediator followed by the OKCC as the second one based on the following assumptions: (a) Following a bottom-up approach in reading ( Gough, 1972 ; LaBerge and Samuels, 1974 ), reading is a process starting from the recognition of the smallest linguistic units (i.e., character) to larger units (words, clauses, sentences, and paragraphs). As hypothesized in the literature, the lexical orthographic knowledge could help readers surpass character-level reading and achieve quickly and fluently comprehend text at higher linguistic levels such as sentence- and text-levels ( Ziegler et al, 2003 ; Jiang et al, 2020 ). Therefore, it was reasonable to arrange the variables with regard to the fine-grained linguistic units; (b) In terms of task difficulty, we considered OKCC was more challenging than OKC to CSL students because they had to additionally recognize characters and understand the context of sentences in order to complete the task.…”
Section: The Present Studymentioning
confidence: 84%
“…Both produced a length effect. Jiang et al (2020) is the only published study so far that was specifically designed to compare L2 and L1 speakers in the area of serial processing in visual word recognition. They examined serial processing in visual Chinese word recognition by means of the stroke number effect.…”
Section: Serial and Parallel Processing In Second Language (L2) Visua...mentioning
confidence: 99%
“…This result may be explained by the stroke-number effect, which proposed that the absence of a stroke-number effect may reflect a parallel or holistic strategy (Jiang et al, 2020). However, there are no consistent results showing that stroke-number effect may affect the recognition of Chinese characters (Jiang et al, 2020). A meta-analysis study compared the learning outcomes of typing and handwriting in Chinese, the results of which revealed that handwriting had positive effects on Chinese learners' orthography recognition and orthography-semantic mapping at both the character and lexical levels (Lyu et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…An empirical study revealed that writing exercises help foreign language learners learn Chinese characters, but stroke order learning may not significantly improve the recognition of Chinese characters (Hsiung et al, 2017). This result may be explained by the stroke-number effect, which proposed that the absence of a stroke-number effect may reflect a parallel or holistic strategy (Jiang et al, 2020). However, there are no consistent results showing that stroke-number effect may affect the recognition of Chinese characters (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%